2008
DOI: 10.1002/0471142301.ns0928s44
|View full text |Cite
|
Sign up to set email alerts
|

The Majchrowicz Binge Alcohol Protocol: An Intubation Technique to Study Alcohol Dependence in Rats

Abstract: Binge drinking of alcohol is an important public health issue, and experimental studies are needed to understand the pathophysiological mechanisms of this problem and develop improved approaches to treatment. This unit presents a validated and widely used method to model binge alcohol drinking in rats. It consists of three daily intragastric administrations of ethanol to rats for 4 days. Ethanol is initially administered at 5 g/kg, and then each subsequent dose is determined based on the degree of intoxication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 14 publications
2
53
0
1
Order By: Relevance
“…According to what previously demonstrated (Majchrowicz, 1975;Ruggeri et al, 2010;Economidou et al, 2011;Faingold, 2008), 12 h after the last alcohol administration, rats showed a significant withdrawal score. Analysis of variance demonstrated a significant overall difference between vehicle and alcohol-treated rats [F(1,24) ¼ 17.47].…”
Section: Experiments 1: Effect Of Allyphenyline Treatment On the Expresupporting
confidence: 56%
“…According to what previously demonstrated (Majchrowicz, 1975;Ruggeri et al, 2010;Economidou et al, 2011;Faingold, 2008), 12 h after the last alcohol administration, rats showed a significant withdrawal score. Analysis of variance demonstrated a significant overall difference between vehicle and alcohol-treated rats [F(1,24) ¼ 17.47].…”
Section: Experiments 1: Effect Of Allyphenyline Treatment On the Expresupporting
confidence: 56%
“…Ethanol (95%) was administered by intragastric intubation in rats in a 30% v/v solution in ISOMIL Infant Formula. Ethanol administration consisted of three doses every 8 h for 4 days, and the levels of intoxication was evaluated using a standard behavior rating scale (Majchrowicz, 1975; Faingold, 2008). The priming dose of ethanol was 5 g/kg (body weight), and the subsequent doses were adjusted for each animal to maintain a moderate degree of ataxia.…”
Section: Methodsmentioning
confidence: 99%
“…At 48 h, when the susceptibility to AWS was no longer present, Ca V channel currents returned to nearly control levels (N’Gouemo and Morad, 2003). Recently, a time-course study reported that AGS susceptibility was absent in the first 7 h but progressively develops after 7 h, peaking at 24 h and disappearing at 48 h during alcohol withdrawal (Faingold, 2008). It is unknown whether the enhanced Ca V channel currents found in IC neurons precedes the onset of AWS susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Es posible que las concentraciones de alcohol en sangre detectadas en los tres grupos de animales de este tratamiento no hayan sido lo suficientemente elevadas como para considerarlas intoxicantes al término del experimento. 44 Dado que en este estudio los animales fueron incrementando progresivamente el consumo de alcohol, es posible que las concentraciones de alcohol en sangre hayan llegado a ser intoxicantes en etapas iniciales e intermedias del tratamiento. Por lo tanto, es indispensable realizar un curso temporal a fin de determinar la concentración de alcohol en sangre a lo largo del tratamiento.…”
Section: Discusión Y Conclusiónunclassified